Combining Postmortem Vitreous Sodium and Chloride and Lung-Body Ratio in Aiding the Diagnosing Saltwater Drowning. (September 2018) - Tse, Rexson; Garland, Jack; Kesha, Kilak; Morrow, Paul; Lam, Leo; Elstub, Hannah; Cala, Allan; Spark, Amy; Palmiere, Cristian; Stables, Simon
Abstract : Abstract: Diagnosing death due to drowning can be difficult, and several postmortem findings have been postulated to aid the diagnosis. Increased lung weights are often seen in drowning deaths. Lung-body (LB) ratio was described to be the best anatomical lung measurement in diagnosing drowning. Postmortem vitreous humor sodium and chloride (PMVSC) was reported to be a useful biochemical test in diagnosing saltwater drowning when the immersion time is less than 1 hour (SWD1). The presented study compared the diagnostic accuracies between LB ratio, PMVSC, and their combination in diagnosing SWD1 in 20 SWD1 and 50 nonimmersion deaths. Classification tree models were used for analysis and revealed that combination of PMVSC and LB ratio was most accurate in diagnosing SWD1 (misclassification rate, 4%), followed by PMVSC (misclassification rate, 10%) and LB ratio (misclassification rate, 24%). A quantifiable diagnostic improvement was established when both LB ratio and PMVSC were used. After adjusting for interlaboratory variations, the developed tree models can be a reliable way in aiding the diagnosis of SWD1. Abstract : Supplemental digital content is available in the text.